Оцінка ефективності систем кондиціонування повітря методом ексергетичного аналізу - Лабай, В.; Іванух, Т. (Видавництво Національного університету «Львівська політехніка», 2000)
Methodics of exergetic analysis of the air conditioning systems is considered in this paper. It was defined that the system with I and II recirculations has highest exergetic efficiency rate in comparison with the system without recirculations and the system having I recirculation.